2022
DOI: 10.1101/2022.04.19.488786
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting gene expression from cell morphology in human induced pluripotent stem cells

Abstract: Purification is essential before differentiating human induced pluripotent stem cells (hiPSCs) into cells that fully express particular differentiation marker genes. High-quality iPSC clones are typically purified through gene expression profiling or visual inspection of the cell morphology; however, the relationship between the two methods remains unclear. We investigated the relationship between gene expression levels and morphology by analyzing live-cell phase-contrast images and mRNA profiles collected dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Integrating gene expression and morphology profiles with chemical structures revealed that each data type provides complementary information for predicting a drug’s mechanism of action (Haghighi et al, 2021; Nassiri and McCall, 2018), for predicting the effects of perturbations (Caicedo et al, 2021a), and for identifying nuisance compounds that can lead to false hits (Dahlin et al, 2021). As well, to some degree, gene expression and morphology datasets contain sufficient information to predict changes in each other (Haghighi et al, 2021; Nassiri and McCall, 2018; Wakui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Integrating gene expression and morphology profiles with chemical structures revealed that each data type provides complementary information for predicting a drug’s mechanism of action (Haghighi et al, 2021; Nassiri and McCall, 2018), for predicting the effects of perturbations (Caicedo et al, 2021a), and for identifying nuisance compounds that can lead to false hits (Dahlin et al, 2021). As well, to some degree, gene expression and morphology datasets contain sufficient information to predict changes in each other (Haghighi et al, 2021; Nassiri and McCall, 2018; Wakui et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The ability to autonomously observe shifts and correlate them to specific events could enable researchers to observe cell health, view the effects of different drug mechanisms, and observe phenotypic plasticity without the need for techniques such as sequencing or fluorescent labeling. One method that has been used on cell populations is autoencoders 16,21,22,44 , which contain a reduced latent space that is representative of the input and have been used for unsupervised learning approaches. Autoencoders have been used primarily to perform latent space predictions and provide explanations for changes in cell morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, image analysis using machine learning has demonstrated that cell-state properties such as metastatic invasion [16][17][18] , the induction of an epithelial to mesenchymal transition 19 , or the introduction of genetic perturbations 20 can be detected through cellular morphology. Notably, deep learning has been effective at learning relevant biological features [21][22][23][24] . Many of these results have been demonstrated only using basic imaging techniques, such as phase contrast or brightfield microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Specific targets for either input labels or annotations could include electrical synapses 74 or more subtle synaptic organelles like multivesicular-endoplasmic reticulum bodies 75 . Given that transcriptional states are strongly correlated with morphological features in cells and tissues [76][77][78][79] , we believe that informative morphological representations such as those produced with SynapseCLR may help form a more complete picture about the connection between structural connectivity and the underlying molecular mechanisms.…”
Section: Synapseclr Representations Suggest New Directions For Future...mentioning
confidence: 99%